Edukasi Program Latihan Keseimbangan Pada Masyarakat Lansia Untuk Menurunkan Risiko Jatuh di Posyandu Pronorogo Lestari Ngamarto RW 7-Lawang - Tri Noor Cahyo Widodo; Novita Lorenza Azahroh; Siti Ainun Ma’rufa; Nadya Setyarini Farizka (Jurnal Pengabdian Masyarakat Nusantara, 2023)
As elderly people age, their body's physiological functions will decrease. Decreased dynamic balance in the elderly can cause a high risk of falls. If this is not addressed, the risk of injury to the elderly will be greater. The aim of this research is to provide education and training to the elderly about dynamic balance and the risk of falls and how to do exercises to reduce these symptoms. This research method was carried out using a community service approach at the elderly posyandu by providing counseling material about "dynamic balance and the risk of falls in the elderly", after that balance measurements were carried out to find out how big the risk of falls was in the elderly and carrying out balance training practices to improve dynamic balance and reduce risk of falling. Counseling and practice regarding dynamic balance and the risk of falls went smoothly, all the elderly who took part in the activity were very enthusiastic and enthusiastic. The education carried out aims to provide knowledge to the elderly about dynamic balance and the risk of falls as well as the benefits of dynamic balance training to prevent the risk of falls in the elderly.